STRATEGI GURU PENDIDIKAN AGAMA ISLAM DALAM MEMBENTUK AKHLAK PESERTA DIDIK KELAS V DI SDN RATO KECAMATAN LAMBU KABUPATEN BIMA - Erni Kurniawati; Martini; Muh. Aidil Sudarmono R; Muhammad Syahrul; Samsuddin Kade (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to determine the strategies of Islamic Religious Education teachers in shaping the morals of fifth-grade students at Rato Elementary School, Lambu District, Bima Regency, as well as the supporting and inhibiting factors. The study used a qualitative approach with data collection techniques in the form of observation, interviews, and documentation. The research subjects consisted of Islamic Religious Education teachers, homeroom teachers, and fifth-grade students. The results showed that the teachers' strategies in shaping the morals of students were carried out through role models, habituation, advice, and supervision. Supporting factors included teacher role models, school support, and religious facilities and activities. Inhibiting factors included limited learning time, environmental and social influences, and lack of parental supervision. It was concluded that the strategies of Islamic Religious Education teachers play an important role in shaping the morals of students and need to be supported by cooperation between teachers, schools, and parents.